Detonating a “time bomb”: how enteric infection stress triggers prophage induction in commensal microbiota and exacerbates disease progression - Yang, Ling; Xu, Yan; Wang, Xinna (Frontiers in Microbiology, 2026)
The pathophysiology of enteric infections involves more than a straightforward pathogen–host interaction; a critical yet often underappreciated factor is the functional shift of the commensal microbiota in response to stress. This review constructs and substantiates a “Prophage-Mediated Implosion Hypothesis” to provide an integrative framework for explaining the complexities of gut infections. This hypothesis posits that during enteric infection, the stress microenvironment—generated by the pathogen, host immune responses, and clinical interventions—transforms the commensal microbiota from a “defensive barrier” into a “destructive endogenous amplifier” via prophage activation. This article systematically elucidates the three core stages of this “implosion” process: (1) how key signaling networks, represented by endogenous DNA damage (e.g., reactive oxygen species [ROS]) and exogenous agents (e.g., antibiotics), trigger the SOS response and activate prophages; (2) how prophage activation disrupts colonization resistance (via commensal lysis), mediates the horizontal transfer of virulence and resistance genes, and exacerbates inflammation (via PAMPs and the TLR9 pathway), thereby creating a destructive cascade; and (3) how this hypothesis offers novel mechanistic explanations for clinical challenges such as antibiotic-associated complications and the heterogeneity in infection severity. Finally, building on this framework, the review discusses emerging intervention strategies—such as antibiotics that spare or support bacteriophage activity and therapies targeting the SOS response to attenuate bacterial virulence. This work aims to shift the understanding of enteric infections from a traditional “external invasion” model to an integrated “combined internal and external assault” model.